Efficacy of Mefipristone for induction of labour in late term pregnancy - K., Roopa N.; N., Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Late-term pregnancy defined as one that has reached between 41 0/7 weeks and 41 6/7 weeks of gestation is associated with an increased maternal morbidity as well as an increased risk of fetal and neonatal mortality and morbidity. Mifepristone, an anti-glucocorticoid and antiprogesterone, though not an oxytocic increases uterine activity and causes cervical effacement and dilatation and improves the Bishop score without over/hyper stimulation of uterus. Increased maternal and fetal mortality from late term pregnancy could be prevented by induction of labour. The objective of this study was to know the efficacy of single dose of oral mifepristone in induction of labour in late term pregnancy and to assess the induction delivery interval in the study population. Methods: This was a prospective interventional study conducted in Department of Obstetrics and Gynaecology at BGS Global Institute of Medical Sciences, Bengaluru. 100 Women with late term pregnancy who fulfilled the inclusion and exclusion criteria were considered for the study after an informed written consent. Results: 73.5% (n=36) of multigravida and 80.4% (n=41) of prim gravida showed improvement in the Bishop score post induction with mifepristone and majority (89.79 % primigravida and 84.31% multigravida) of the study population had vaginal delivery. Multigravida (73.5%) had less induction delivery interval (less than 48hours) compared to primigravida (19.6%). Conclusions: Mifepristone, a progesterone antagonist causes a significant improvement in the Bishop’s score and is associated with an increased rate of vaginal deliveries.